General Relativistic Study of Motion of Comets Particles Elliptical Gravitational Field - Timothy Bulus; Chifu E Ndikilar; Halliru Ibrahim; Dayyabu Tafida (Physics Access)
Comets are small bodies consisting of aggregates of ice mixed with rock and dust. They are usually influenced by galactic forces and stellar encounters, and may have contributed to the formation of ice giants and transport gases across the solar system. Their orbits vary widely, and their frozen water sublimates around 3 AU, forming a coma, though some remain active beyond this distance. In this study, the line element in the gravitational field due to a static and ellipsoidal isolated gravitating mass point was used to study the motion of comets, and the relativistic equation of motion of an ellipsoidal mass was obtained via the metric tensor, affine connections and geodesics equation. The results show that the explicit equations of comets along the equatorial plane are second-order differential equations similar to reported results in the literature for different gravitational fields.